The urgency of nurse-based peritoneal dialysis unit in remote areas a case study - Ramli Muhammad (Institute of Computer Science (IOCS), 2023)
The trend of prevalence rate increase of Chronic Kidney Disease (CKD) with dialysis therapy which is not matched by the availability of adequate peritoneal dialysis units in the community will risk increasing patient morbidity and mortality. Meanwhile, the number of trained dialysis nurses is very limited. The objective is to obtain an overview of nurses' opinions regarding the concept of establishing a nursing-based CAPD unit. This research used a case study method with a descriptive design. Data were obtained through in-depth interviews conducted with 4 nurses from Papua, North Sulawesi, South Sulawesi, and East Java. The instrument was an in-depth interview guide. The dependent variable of the study was the CAPD unit and the independent variables were PD nurses and rural areas. Data were analyzed using the Rapid Assessment Procedures (RAP) model. The results of this study showed that the four informants agreed on four problems related to the urgency of establishing a CAPD unit under nurse management, namely the understanding of the term CAPD with limited socialization, the absence of training for general nurses, the role of general nurses was not yet arranged in a standard operating procedure (SOPs), and the requirements for establishing a CAPD unit by nurses were not yet available. The study recommended the importance of establishing CAPD units under the management of trained nurses, the supervision of certified CAPD nurses, and CAPD consultants, in addition to fulfilling other administrative and technical requirements.